Divergent Synthesis of Various 2-Aryl Iminocyclitols from (R)-p-Hydroxyphenylglycine - Jain, Vipin Kumar (Synthesis, 2019)
A concise and efficient synthesis of various 2-aryl iminocyclitols is reported from (R)-p-hydroxyphenylglycine using Upjohn dihydroxylation and base-promoted intramolecular cyclization. These 2-aryl iminocyclitols are the important structural framework of various bioactive compounds and also known as glycosidase inhibitors.
Keywords: Upjohn dihydroxylation; alkaloids; iminocyclitols; diastereoselectivity; glycosidase inhibitor